Decoding investment behavior: The impact of financial literacy, risk tolerance, and financial satisfaction on generation z’s investment decisions - Pratama, I Wayan Rian; Artini, Luh Gede Sri (International research journal of management, IT and social sciences, 2025)
The investment decision is a decision to allocate a certain amount of funds in a particular type of investment to generate profits in the future. Accessing technology-based financial services, known as fintech, makes the process of investing in financial securities feasible. This study will analyze the investment behavior of Generation Z investors by examining the factors that influence investment decisions based on the theory of financial planning behavior and prospect theory. This research is conducted in Denpasar with a participant sample of 260 Generation Z investors, which was then analyzed using the SEM-PLS method. The findings show that Financial Satisfaction, Risk Tolerance, Financial Literacy, and Investment Intention have a direct positive effect on Investment Decisions. Financial Satisfaction and Financial Literacy have a positive effect on Investment Intention; however, Risk Tolerance has a significant negative effect on Investment Intention. This study also found that Investment Intention acts as a mediator between Financial Satisfaction and Financial Literacy on Investment Decision, not between Risk Tolerance and Investment Decision. The Indonesia Stock Exchange Investment Gallery (IDX) and financial institutions ought to understand Generation Z’s investing behavior. By understanding this behavior, they can help issuers identify opportunities to attract young investors.